Membaca Citra Indonesia Dalam Arsip Audio Visual Kementerian Pariwisata - Rina Widiastuti; Lastria Nurtanzila (Diplomatika: Jurnal Kearsipan Terapan, 2018)
This article aims to explore the image of Indonesia created by the Ministry of Tourism through the audio-visual archive, which is stored and published on its official youtube channel. This study is in response to the Indonesian government's policy to improve the image of Indonesia and build a strong nation brand for Indonesia to compete in global level. Using the content analysis method, I analyzed the videos on the Indonesia.Travel channel to reveal the image of Indonesia promoted by the Indonesian government. Based on the icons that appear on the 218 videos on the youtube channel, we can find five main icon categories. The iconic categories are natural beauty, cultural uniqueness, resident friendliness, delicacy of food, and environmental peace. These five iconic categories build one image of Indonesia as a wonderful country. This is in accordance with the official slogan used by the Ministry of Tourism to promote Indonesia, namely Wonderful Indonesia.Artikel ini bertujuan untuk mengeksplorasi arsip audio-visual yang disimpan dan dipublikasikan di saluran resmi youtube. Penelitian ini merupakan tanggapan terhadap kebijakan bahasa Indonesia untuk meningkatkan citra Indonesia dan membangun kebangsaan yang kuat bagi Indonesia untuk bersaing di tingkat global. Menggunakan metode analisis isi, saya menganalisis video di Indonesia. Saluran perjalanan untuk mengungkap citra Indonesia dipromosikan oleh pemerintah Indonesia. Berdasarkan ikon yang muncul pada 218 video di saluran YouTube, kita dapat menemukan lima kategori ikon utama. Kategori ikonik adalah keindahan alam, keunikan budaya, keramahan penduduk, kelezatan makanan, dan kedamaian lingkungan. Kelima kategori ikon citra Indonesia sebagai negara yang indah. Hal ini sesuai dengan slogan resmi yang digunakan oleh Kementerian Pariwisata untuk mempromosikan Indonesia, yaitu Wonderful Indonesia.